The Benefits of Active Video Games for Educational and Physical Activity Approaches: A Systematic Review - Carlos Merino-Campos; Héctor del Castillo Fernández (Springer, 2016)
This article sets out to conduct a systematic review of the current literature on active video games as potential educational tools for physical education or physical activity. To begin with, research on active video games for educational and physical purposes has been examined with the purpose of verifying improvement of attitudes, intellectual skills, knowledge, motor skills and physical properties associated with physical activity and physical education. A second aim will be to determine the effectiveness of active video games compared with traditional approaches to physical activity. From this perspective, a systematic literature search from relevant international databases was conducted from January to July 2015 in order to find papers published in journals or conference proceedings from January 2010 onwards. Then, 2648 references were identified in database searches and 100 of these papers met the inclusion criteria. Two main conclusions are to be drawn from this research. Firstly, controlled studies demonstrate that active video games increase capacities in relation to physical activity and education. Secondly, Research also shows that physical activity interventions designed and measured using behavioural theories are more likely to be successful in comparison with traditional exercise activities.